Effect of Chitosan Incorporated with Natural Oils on Physicochemical Properties of Ready-to-Eat Shrimp - Norizan, Siti Nurhaziqah; Zainal Abidin, Munira (Enhanced Knowledge in Sciences and Technology, 2023)
Ready-to-eat (RTE) shrimp is a highly perishable aquatic animal with short shelf-life. The chitosan edible coatings have been found for having the great antimicrobial properties for food protection and preservation. However, their uses are currently limited owing to their hydrophilic character and weak water resistance. Thus, to improve water-barrier properties of chitosan coating and extend the shelf- life of RTE shrimp by minimizing the deterioration, the hydrophobic compounds (lipids), such as lemon essential oil and olive oil are incorporated in the chitosan coating. Initially, the shrimps were cooked in boiling water for 2 minutes until it reached a temperature of 63°C. Then, RTE shrimps were dipped in chitosan solution mixed with lemon essential oil or olive oil for 5 mins and stored at 6±1 ºC to determine the most effective mixture of chitosan coating with plant oil that can reduce the colony forming of Escherichia coli (E. coli) and improve shelf-life of the shrimps stored at 6±1 ºC. The viability of the coating in extending the shrimp shelf life was assessed by evaluating pH, color and texture during the storage period. Chitosan edible coating incorporated with lemon essential oil (CL) had a better outcome on pH, color and texture as compared to only chitosan coating (C) and chitosan coating incorporated with olive oil (CO) (p<0.05) toward the end of storage. This investigation showed that chitosan coating incorporated with lemon essential oil was more effective in prolonging the shelf-life and quality of shrimp during the entire storage period than chitosan coating or chitosan incorporated with olive oil.